Drivers of long-term insecurity and instability in Pakistan : urbanization - Blank, Jonah (RAND, 2014)
Already one of the most urbanized nations in South Asia, Pakistan is projected to have a majority of its population living in cities within three decades. This demographic shift will alter Pakistan's politics and threaten its stability, but the political and security implications of Pakistan's urbanization remain underanalyzed. This report examines urbanization as a potential driver of long-term insecurity and instability, with particular attention to the cities of Karachi, Lahore, and Quetta. Drawing on demographic trends, election results, and survey data, the authors conclude that urbanization may fuel anti-American sentiment and help recruitment by transnational Islamist groups (but not necessarily Islamist political parties) in the short term. Urbanization is also likely to increase popular demand for political reform in Pakistan. In the near future, a Pakistani government more directly accountable to its electorate might be less willing to cooperate with the United States in unpopular security policies. In the long run, however, a Pakistani government more responsive to its citizens could be a better security partner for the United States. By spurring Pakistani policymakers to focus on provision of good governance and public services rather than on scapegoating external actors, political reform may eventually help reduce anti-American attitudes.